2021
DOI: 10.1111/jfbc.13765
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl disulfide ameliorates methotrexate‐induced nephropathy in rats: Molecular studies and network pharmacology analysis

Abstract: Methotrexate (MTX) is a promising chemotherapeutic agent. Its medical use is limited by induced nephropathy. Our study was designed to explore the reno‐protective effect of diallyl disulfide (DADS), an organosulfur compound of garlic oil, on MTX‐induced nephropathy. Adult rats were randomly divided into 4 groups; normal control, DADS (50 mg kg–1 day–1, p.o.), MTX (20 mg/kg, i.p.) and DADS+MTX. DADS significantly decreased serum creatinine, urea, uric acid, and albumin levels with an improvement of final body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…In our investigations, we observed a significant drop in the activity of the CAT and SOD enzymes, as well as a decrease in the levels of GSH and ATP in the MTX-treated groups. These results are in agreement with previous studies that reported that MTX treatment led to reduced GSH, SOD, and CAT activity, as well as elevated MDA [50][51][52]. Notably, the magnitude of GSH detected (pg/g tissue) in our experiments is lower than previously reported studies values.…”
Section: Discussionsupporting
confidence: 93%
“…In our investigations, we observed a significant drop in the activity of the CAT and SOD enzymes, as well as a decrease in the levels of GSH and ATP in the MTX-treated groups. These results are in agreement with previous studies that reported that MTX treatment led to reduced GSH, SOD, and CAT activity, as well as elevated MDA [50][51][52]. Notably, the magnitude of GSH detected (pg/g tissue) in our experiments is lower than previously reported studies values.…”
Section: Discussionsupporting
confidence: 93%
“…Then, the Huisgen 1,3-dipolar cycloaddition reaction condition (CuI/Et 3 N/CH 2 Cl 2 ) was employed to prepare glycoconjugated triazole-phthalimides F2, F3 and F4 in good yields (68-90%). The molecular structure of the phthalimide syntheses was confirmed by IR, 13 C NMR, and 1 H NMR by the similarity of the spectra reported by Assis et al [33] and Silva Júnior et al [34].…”
Section: Discussionsupporting
confidence: 63%
“…The infrared spectra were recorded on an IFS66 Bruker spectrophotometer using KBr discs. 1 H and 13 C NMR were obtained on Varian Unity Plus-300 and Varian UNMRS 400 MHz spectrometers using CDCl 3 or DMSO-d 6 as a solvent. The polarimeter used was the Krüss, of 10 cm path length and a concentration of the solution in g/100 mL.…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations